The rare malformation holoprosencephaly: pathogenesis, association with pregestational diabetes and the possible link with food pollutants - Domenica Taruscio; Alberto Mantovani (Istituto Superiore di Sanità, 2023)
Background. Holoprosencephaly is a rare (1/16,000 livebirths) and severe brain malformation occurring during early embryogenesis. The malformation originates from absent or incomplete forebrain division and is associated with altered embryonic patterning. Objectives. A narrative review to identify and assess the evidence on non-genetic risk factors. Results. Genes involved include sonic hedgehog, Zinc finger protein, SIX homeobox 3. Pregestational diabetes, with periconceptional hyperglycaemia, is the main non-genetic  risk factor; increased oxidative stress in neuroectoderm, in particular neural crest cells, appears as the main mechanism. Several widespread pollutants, including inorganic arsenic, PFAS and PCBs, may increase the risk of pregestational diabetes by altering metabolic factors, including lipids and insulin. A scenario "widespread exposures-rare outcomes in susceptible subjects" suggests that exposure to dietary pollutants may increase the risk of pregestational diabetes, hence of holoprosencephaly in susceptible embryos. Conclusions. This complex pathway is plausible and worth being investigated; moreover, it highlights the importance of assessing risk factors, and the associated uncertainties,  in order to support primary prevention strategies for multifactorial malformations.